PENGARUH PROFITABILITAS, LIKUIDITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN PENGUNGKAPAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN ENERGI DI BEI PERIODE 2019-2023 - Waode Maya Anggelya Putri; Rico Wijaya; Misni Erwati (Komunitas Manajemen Kompetitif, 2026)
This research investigates the empirical impact of profitability, liquidity, and leverage on firm value, while concurrently evaluating the moderating capacity of Good Corporate Governance (GCG) within these dynamics. The study focuses on energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. Employing a quantitative methodology, this study utilizes Structural Equation Modeling (SEM) based on Partial Least Square (PLS) via WarpPLS 8.0 software. Through a purposive sampling technique, 26 companies were selected, yielding a longitudinal dataset of 130 observations over a five-year horizon. The empirical findings demonstrate that: (1) Profitability exerts a significant influence on firm value; (2) Liquidity has a significant negative impact on firm value; and (3) Leverage significantly affects firm value. However, the moderation analysis reveals that Good Corporate Governance fails to moderate the relationship between profitability, liquidity, or leverage and firm value within the energy sector during the observedperiod.